PROFESSOR PETRE T. FRANGOPOL – A BRIEF, PERSONAL ACCOUNT ON THE LEGACY HE LEFT IN IAŞI - LUCHIAN, Tudor (Studia Universitatis Babeș-Bolyai Chemia, 2021)
More than about a man, this evocation is about some of the ideas, ideals and legacy that will ever define that man. I met Professor Petre T. Frangopol while I was still an undergraduate student, and both our approaches toward one another were short-sentenced, straight, sincere and even blunt. Professor Frangopol was in the incipient phase of developing a new specialization at the Faculty of Physics in Iaşi, and thus in worried need of young, talented, hard-working people able to take on the challenge, while I was in the pursuit of a dream, namely to do research in biophysics. Apparently, we were both in luck those days. As discussions progressed, I still remember vividly the central question Professor Frangopol kept asking me: “...if you would have a lab, what project will you be able to start at once? What’s your plan?” Early on our endeavor, I have also heard for the very first time about notions such as curriculum vitae, quality research based on original ideas and not re-vamped projects imported from other labs, the need to respect intellectual qualities of other people despite personal judgements, the need to compare ourselves with the best in our field, to mention very few. Needless to say, I didn’t have much of a clue of what biophysics was about, beyond the scarce literature I was able to access and read in the library. As for the infrastructure needed to propel my ‘to be’ ideas, it was totally absent. Things one gets for granted nowadays in even a modest lab, as a minimal start-up on a research pursuit (e.g., a decent computer, some measuring devices and essential reagents, etc.), were only present … in some leaflets and books found in some corridors of the Faculty.